2015
DOI: 10.1142/s021821651550011x
|View full text |Cite
|
Sign up to set email alerts
|

Knot projections with a single multi-crossing

Abstract: An n-crossing is a singular point in a projection of a link at which n strands cross such that each strand travels straight through the crossing. We introduce the notion of an ubercrossing projection, a knot projection with a single n-crossing. Such a projection is necessarily composed of a collection of loops emanating from the crossing. We prove the surprising fact that all knots have a special type ofübercrossing projection, which we call a petal projection, in which no loops contain any others. The rigidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 10 publications
1
53
0
1
Order By: Relevance
“…It is of interest to understand the relation between the crossing number c(K) of a knot and the least number of petals p(K) needed to represent it. We show in EvenZohar et al (2017a) that pðKÞ OðcðKÞÞ, and this bound is tight by results of Adams et al (2015a). They have also shown that cðKÞ Oðp 2 ðKÞÞ, which is also tight.…”
Section: The Petaluma Modelsupporting
confidence: 74%
See 3 more Smart Citations
“…It is of interest to understand the relation between the crossing number c(K) of a knot and the least number of petals p(K) needed to represent it. We show in EvenZohar et al (2017a) that pðKÞ OðcðKÞÞ, and this bound is tight by results of Adams et al (2015a). They have also shown that cðKÞ Oðp 2 ðKÞÞ, which is also tight.…”
Section: The Petaluma Modelsupporting
confidence: 74%
“…A random knot in the star model is generated by randomizing the ðn À 1Þð2n þ 1Þ crossings. Star diagrams are plane isotopic to closed n-braids (Adams et al 2015a), as demonstrated in Fig. 12b, c. The star model yields all knots, since the Petaluma model does, but with quite different distribution.…”
Section: Crisscross Constructionsmentioning
confidence: 85%
See 2 more Smart Citations
“…Common models are based on random 4-valent planar graphs with randomly assigned crossings, random diagrams on the integer grid in R 2 , Gaussian random polygons [10,5,29], and random walks on lattices in R 3 [35,33]. While many interesting numerical studies have been performed, and interesting results obtained in these models, there have been few rigorous derivations of associated statistical measures.In this paper we study a model of random knots and links called the Petaluma model, based on the representation of knots and links as petal diagrams that was introduced by Adams and studied in [2]. The Petaluma model has the advantage of being both universal, in that it represents all knots and links, and combinatorially simple, so that knots have simple descriptions in terms of a single permutation.…”
mentioning
confidence: 99%